Metal machining : theory and applications - Childs, Thomas (Arnold ; John Wiley & Sons, 2000)
Discusses the theory and application of metal machining. It begins with an overview of the development of metal machining and its role in the current industrial environment and continues with a discussion of the theory and practice of machining. The underlying mechanics are analyzed and applications are examined through a discussion of simulation and process control.